Between the Family and Politics: Female Politicians as Media Objects in Bollywood Films. (January 2017) - Rasul, Azmat
Abstract: Of late, researchers have examined the stereotyping of female politicians in entertainment media as a serious problem in several democratic societies. Despite chauvinism and stereotyping, the entertainment industries find female politicians attractive content producers, which guarantee tangible profit, as audiences are interested in learning about the life stories of female politicians. This article employs feminist political economy of communication to analyse exposé of female politicians in three Bollywood chick flick movies featuring lead characters in important political positions. This study finds that chick flicks—movies centred on attractive female lead characters and typically marketed to women—serve as a mechanism to sell commercial entertainment products to both female and male audiences. I argue that Bollywood's political movies are marketed through a focus on bodily attributes of female politicians that helps perpetuate patriarchal ideology in which women are passive homemakers and effectively domesticated and excluded from public sphere.